Creating Undocumented EU Migrants through Welfare: A Conceptualization of Undeserving and Precarious Citizenship. (June 2018) - Lafleur, Jean-Michel; Mescoli, Elsa
Following the financial and economic crisis, welfare policies across the EU are increasingly becoming instruments for limiting the mobility of certain EU migrants. In this article, we focus on EU citizens who see their freedom of movement in the EU being restricted after they have applied for social assistance or unemployment benefits in their country of residence. Doing so, we conceptualize undocumented EU migration by means of the concepts of 'non-deportability', 'deservingness' and 'precariousness'. Overall, this article – based on ethnographic fieldwork conducted with Italian migrants in Belgium – expands our understanding of undocumented migration by demonstrating how arbitrary and intimidating bureaucratic processes undermine the exercise of EU citizenship.